Droplet organelles?. (29th June 2016) - Courchaine, Edward M; Lu, Alice; Neugebauer, Karla M
Abstract: Cells contain numerous, molecularly distinct cellular compartments that are not enclosed by lipid bilayers. These compartments are implicated in a wide range of cellular activities, and they have been variously described as bodies, granules, or organelles. Recent evidence suggests that a liquid–liquid phase separation (LLPS) process may drive their formation, possibly justifying the unifying term "droplet organelle". A veritable deluge of recent publications points to the importance of low‐complexity proteins and RNA in determining the physical properties of phase‐separated structures. Many of the proteins linked to such structures are implicated in human diseases, such as amyotrophic lateral sclerosis (ALS). We provide an overview of the organizational principles that characterize putative "droplet organelles" in healthy and diseased cells, connecting protein biochemistry with cell physiology. Abstract : Non‐membrane‐bound cellular structures such as nucleoli, stress granules, Cajal and P bodies have been long established. Recent data reviewed by Neugebauer and colleagues delineate liquid–liquid phase separation processes that underlie the dynamic nature of these organelles composed of low‐complexity proteins and RNA.